Challenges of simulation for buildings energy performance survey in Sub-Saharan Africa - (:unkn) unknown (My University, 2015)
In sub-Saharan African countries, the energy context, the high urban growth, inadequate construction techniques and climate offer great potential for bio-climatic approach and sustainable construction particularly on the energy level. However, this potential and the use of passive cooling techniques are weakly explored. To do so, it requires a good knowledge of building’s behaviour and their adaptation to the climatic context. As part of our contribution to this issue, a study on the thermal behaviour of buildings is initiated by numerical simulation. Indeed the building’s energy performance simulation tools are becoming more essential in the building’s design processes and analysis. Investigations are conducted on a building built with typical materials in Burkina Faso by following two main approaches. In the first approach a model of the building is faced with measurements from field experiments on the building. A calibration methodology based on the sensitivity analysis and optimization has been applied for the comparison of results. This helped to calibrate the model and diagnostic studies are performed.In the second approach, investigations on methods which can help to improve the building performance are realized through the application building performance simulation as a design aid tool. Interoperability and optimization techniques are used to deal with passive cooling techniques and their impacts on the building thermal behaviour are assessed. Finally in this work analysis techniques and performance criteria are used to characterize and make recommendations on building designs for the tropical climate context.
Keywords: African Research